Implementasi Metode Montessori dalam Keterampilan Kognitif Anak Usia Dini di Taman Kanak-kanak Windsor Montessori Palembang - Ayu Putri, Rizky; Marlina , Leny; Oktamarina, Lidia; Izza Fitri; Ayu putri , Rizky (Al-Mudarris, 2026)
This study examines the implementation of the Montessori method in developing early childhood cognitive abilities at TK Windsor Montessori Palembang. The research is grounded in the assumption that learning methods in early childhood education must be responsive to children’s developmental needs and holistic growth. Employing a qualitative case study design, data were collected through in depth interviews, participatory observations, and documentation. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings reveal that Montessori-based learning at TK Windsor Montessori Palembang is systematically planned and thematically organized in accordance with Montessori principles, emphasizing hands-on learning, sensory exploration, and children’s independence. In practice, learning activities are implemented naturally and flexibly, allowing children to actively engage in problem solving, logical reasoning, and symbolic thinking through meaningful real life experiences. Cognitive development is assessed through continuous and authentic observation rather than formal testing, enabling teachers to capture children’s thinking processes and learning strategies. From the perspective of Islamic education, the Montessori approach contributes not only to cognitive development but also to the formation of character, discipline, responsibility, and self regulation, which align with the Islamic concept of tarbiyah and holistic human development. The integration of cognitive, moral, and social dimensions supports the nurturing of learners who are intellectually capable, ethically grounded, and spiritually aware. This study highlights the relevance of Montessori pedagogy as an alternative child centered approach that is compatible with the goals of Islamic early childhood education.